Mapas auto-organizáveis na construção de recursos de aprendizagem adaptativos: uma aplicação no ensino de música - Ferreira, Fabiano Rodrigues (2008)
Brazilian educational scenario suffers from the lack of incentive to a musical apprenticeship that leads students to reflect about their own reality. Due to the actual hegemonic politics, educational processes, in general, are characterized by diminishing student s potential for reflection, in a society that priorizes a strict technicist teaching, as contemporary society is. As a result, students are often not able to stablish relationships between what was learned and their own lives. Thus, it is necessary to have some mechanisms that could help the adaptation to student s cultural context, leading to a meaningful ethnic learning. Learning objects concept can be understood as examples of technological resources that appear in a way to organize and structure digital educational data. Such concept, althought is a new paradigm into educational ambit, has been widely used on educational systems by constant & crescent deliver of learning objects by Internet. In this way, this work focuses an adaptive learning object architecture, applied to the learning process of Brazilian musical rhythms, as an example. Such objects are dynamically retrieved from repositories through techniques based on self-organizing maps. Objects are selected in order to create learning resources adequate to some desirable adaptivity factor, as previous knowledge, learning styles or cultural aspects.